2002
DOI: 10.1074/jbc.m207402200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the 47-kDa Lipoprotein of Treponema pallidum Reveals a Novel Penicillin-binding Protein

Abstract: Syphilis is a complex sexually transmitted disease caused by the spirochetal bacterium Treponema pallidum. T. pallidum has remained exquisitely sensitive to penicillin, but the mode of action and lethal targets for ␤-lactams are still unknown. We previously identified the T. pallidum 47-kDa lipoprotein (Tp47) as a penicillin-binding protein (PBP). Tp47 contains three hypothetical consensus motifs (SVTK, TEN, and KTG) that typically form the active center of other PBPs. Yet, in this study, mutations of key amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 52 publications
(31 reference statements)
0
42
0
1
Order By: Relevance
“…In our recent study of TP0326/BamA (19), we determined the mean copy number of tprC transcript to be 212 Ϯ 35 per 10,000 copies of flaA. Although more than 3-fold greater than levels of tp0326 transcript (61 Ϯ 16), this value is markedly lower than the more than 2,500 flaA-normalized copies of tp0547 message, which encodes the abundant lipoprotein carboxypeptidase Tp47 (17,19). Expression of TprC on a per-cell basis was here determined by quantitative immunoblot analysis (Fig.…”
Section: Tprc Is Trimeric and Forms Channels In Large Unilamellar Vesmentioning
confidence: 76%
“…In our recent study of TP0326/BamA (19), we determined the mean copy number of tprC transcript to be 212 Ϯ 35 per 10,000 copies of flaA. Although more than 3-fold greater than levels of tp0326 transcript (61 Ϯ 16), this value is markedly lower than the more than 2,500 flaA-normalized copies of tp0547 message, which encodes the abundant lipoprotein carboxypeptidase Tp47 (17,19). Expression of TprC on a per-cell basis was here determined by quantitative immunoblot analysis (Fig.…”
Section: Tprc Is Trimeric and Forms Channels In Large Unilamellar Vesmentioning
confidence: 76%
“…3). Changes in the intrinsic fluorescence of recombinant TroA, a periplasmic ABC metal-binding protein of T. pallidum (8,19), or Tp47, a T. pallidum periplasmic penicillin-binding protein (9,46), in the presence of D-glucose were below 2% (not shown). In comparison with all of these baseline (negative control) values, the intrinsic fluorescence of Tp38 changed markedly only in the presence of D-glucose or D-galactose (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant TroA was purified from E. coli as previously described (8). Recombinant Tp47 was isolated according to previously published methods (9).…”
mentioning
confidence: 99%
“…Analysis of the T. pallidum genome sequence predicts three putative PBPs but no typical ␤-lactamases (17). However, Cha et al (8) showed that Tp47, an abundant, membrane-bound lipoprotein that was initially identified and characterized by Norgard and colleagues (12,82), binds penicillin and has high ␤-lactamase activity that is subject to strong product inhibition. Furthermore, Cha et al (8) hypothesized that if a mutant variant of Tp47 emerges that overcomes the product inhibition of its ␤-lactamase activity, this would confer novel, bona fide resistance to penicillin.…”
Section: Potential Mechanisms For Development Of Resistance To Tetracmentioning
confidence: 99%